2001
DOI: 10.2746/042516401776767403
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal radiography in monitoring the resolution of sand accumulations from the large colon of horses treated medically

Abstract: Summary This retrospective study consisted of 14 horses (age 6 weeks–12 years) with radiographically evident sand accumulations cranioventrally in the abdomen and clinical signs suggestive of sand enteropathy. The horses were treated medically and resolution of sand was monitored radiographically. Routine treatment consisted of psyllium mucilloid, combined with magnesium sulphate and/or mineral oilif needed. Initially, the number, size and shape of the sand accumulations showed large variation and the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 10 publications
3
49
1
3
Order By: Relevance
“…In most instances, sand is ingested accidentally as a result of feeding hay from the ground (Colahan 1987). Medical management is usually the primary treatment for sand impaction in horses with surgical intervention indicated in only a small percentage of cases (Ragle and others 1989, Ruohoniemi and others 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In most instances, sand is ingested accidentally as a result of feeding hay from the ground (Colahan 1987). Medical management is usually the primary treatment for sand impaction in horses with surgical intervention indicated in only a small percentage of cases (Ragle and others 1989, Ruohoniemi and others 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Medically treated horses were likely often discharged from the ISME equine hospital before the sand could be eliminated completely. Studies showed that using a combination of magnesiumsulfate and psyllium or mineral oil and psyllium as a laxative can eliminate sand from the large colon within four days (Hotwanger et al 2008, Niinistö et al 2014, Ruohoniemi et al 2001. Our follow-up control radiographs were performed at least four weeks after discharge from the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of sand enteropathy can be challenging and typically involves several of the following tests: general clinical examination including abdominal auscultation and rectal palpation, fecal sedimentation test, abdominal ultrasonography and radiography or exploratory laparotomy (Höppner et al 2001, Keppie et al 2009, Korolainen et al 2002, Ragle et al 1989, Ruohoniemi et al 2001. Medical and surgical treatment protocols for sand impaction have been described with good short-term survival, resulting in 85 -90 % of horses reported to be discharged from their hospitals after therapy of sand-gastroenteropathy (Granot et al 2008, Hammock et al 1998, Hart et al 2013, Höppner et al 2001, Hotwanger et al 2007, Maxwell et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Psyllium is often recommended for horses as a preventative strategy for sand colic (Bertone et al 1988, Ragle et al 1989, Ruohoniemi et al 2001 although two separate studies failed to find any beneficial effect of this treatment (Hammock et al 1998, Lieb & Weise 1999. Additionally, feeding of forage on the ground in sandy pastures or access to sandy ponds and streams might also increase sand consumption.…”
Section: Intestinal Impactions and Displacementsmentioning
confidence: 99%